The OPTIMALISASI STRATEGI PROMOSI UMKM LOKAL MELALUI GOOGLE TRENDS: PROGRAM PELATIHAN DAN PENDAMPINGAN BERBASIS DATA: Abstrack - Noventa, Oscar; Novianto Haribowo, Ignatius; Yudistya Wardhana, Daniel; Aribawa, Dwitya; Yustino Setiawan, Wimpie; Indra Kristianto, Ignatius (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) supported by St. Yusup Bintaran Parish in Yogyakarta to utilize digital technology for data-driven marketing strategies. The main challenges faced by local MSMEs include low levels of digital literacy, limited access to market analysis tools, and a reliance on traditional promotional methods. In response to these challenges, the Community Service Team (Abdimas) from the Faculty of Business and Economics, Atma Jaya Yogyakarta University (FBE UAJY), in collaboration with the Social and Economic Development Unit (PSE) of the parish, designed a training program focused on the use of Google Trends. The program was implemented over seven structured sessions, covering needs assessment, introduction to digital tools, practical market trend analysis, strategy formulation, and intensive coaching. The training resulted in improved participant understanding and skills in interpreting search trend data, identifying relevant keywords, and designing more targeted digital marketing strategies. Through a practical and contextual approach, this program is expected to support the digital transformation of local MSMEs and strengthen their competitiveness in the digital economy era.